DECONSTRUCTING ISLAMIC REASONS: ARKOUN’S CRITIQUE AND IBN SINA’S PHILOSOPHY OF THE SOUL - Said, Basnang; Fauzi, Ipan; Khori, Ahmad; Qulyubi, M. Mujib (Sekolah Tinggi Agama Islam Sadra, 2025)
Amid ongoing debates on the critical re-evaluation of the Islamic intellectual tradition, this paper directly addresses the need for a deconstructive approach by analyzing Ibn Sīnā’s philosophy of the soul through Mohammed Arkoun’s hermeneutics to expose the power-knowledge nexus in its epistemological foundations. The research pursues three objectives: first, to dissect Ibn Sīnā’s conception of the soul critically; second, to evaluate Arkoun’s critique of religious reason—particularly his concept of l’impensé—in the deconstruction of metaphysical assumptions; and third, to formulate a methodological synthesis that bridges philosophical-textual analysis with ideological critique. Utilizing philosophical-critical hermeneutics, the study proceeds through three stages: a systematic reconstruction of Ibn Sīnā’s arguments, a deconstructive analysis through Arkoun’s lens, and a contextual critique within contemporary discourse. The findings suggest that Ibn Sina’s theory subtly reinforces epistemic hierarchies aligned with the scientific paradigm of his era. Arkoun’s method, while demanding adjustments for dense philosophical texts, proves effective in unsettling inherited intellectual dogmas. As a result, the study proposes a hybrid analytical model that offers both critical depth and constructive engagement with classical Islamic texts. This contributes to rethinking Islamic philosophy in ways relevant to education, intellectual renewal, and interfaith dialogue. The research also points to fertile ground for further inquiry—particularly the application of this hybrid method to other classical thinkers and the expansion of its scope through interdisciplinary integration.